Fluorine in Shark Teeth: Its Direct Atomic‐Resolution Imaging and Strengthening Function1. (20th January 2014) - Chen, Chunlin; Wang, Zhongchang; Saito, Mitsuhiro; Tohei, Tetsuya; Takano, Yoshiro; Ikuhara, Yuichi
Abstract Atomic‐resolution imaging of beam‐sensitive biominerals is extremely challenging, owing to their fairly complex structures and the damage caused by electron irradiation. Herein, we overcome these difficulties by performing aberration‐corrected electron microscopy with low‐dose imaging techniques, and report the successful direct atomic‐resolution imaging of every individual atomic column in the complex fluorapatite structure of shark tooth enameloid, which can be of paramount importance for teeth in general. We demonstrate that every individual atomic column in shark tooth enameloid can be spatially resolved, and has a complex fluorapatite structure. Furthermore, ab initio calculations show that fluorine atoms can be covalently bound to the surrounding calcium atoms, which improves understanding of their caries‐reducing effects in shark teeth.